Influence of the toxic effect of zinc and mineral starvation on the growth and development of buckwheat plantlets in vitro - S. А. Borovaya; A. G. Klykov; E. N. Barsukova (Труды по прикладной ботанике, генетике и селекции)
Background. Common buckwheat is a cereal crop with high potential for genetic improvement in terms of developing breeding material resistant to abiotic stressors. To date, there have been no reports on in vitro production of buckwheat plantlets resistant to high doses of zinc and a lack of macronutrients.   Materials and methods. Aseptic single-node cuttings from the obtained regenerated plants of common buckwheat cultivars ‘Dikul’ and ‘Izumrud’ were cultivated in vitro on nutrient media with the addition of the selection factor ZnSO4 × 7 H2O in a concentration of 808–1313 mg/L. Survived plants were microcloned on nutrient media without macrosalts for mineral starvation modeling. Morphological traits and general nonspecific adaptation reactions of the plantlets were evaluated for the following characteristics: plant height, the number of internodes, the number of leaves, leaf blade length, the presence of roots, and leaf color.   Results. According to the results of the 33-day cultivation of test-tube microcuttings on media with zinc toxicity, 33–91 % of lines resistant to ionic stress were selected in different variants. The secondary testing of the plantlets under conditions of mineral starvation in vitro turned out to be the strongest inhibitory factor for buckwheat. At the same time, high resistance to stress was observed in cv. ‘Dikul’. Cultivation of the obtained buckwheat lines on the MS nutrient medium for two passages showed a sufficiently high level of regeneration in the studied genotypes. The test-tube buckwheat plantlets obtained under selective conditions are promising material for further breeding as well as for studying the possibility of their use as phytoremediators.